The Identification of DepB: An Enzyme Responsible for the Final Detoxification Step in the Deoxynivalenol Epimerization Pathway in Devosia mutans 17-2-E-8 - Carere, Jason; Hassan, Yousef I.; Lepp, Dion; Zhou, Ting (Frontiers in Microbiology, 2018)
Deoxynivalenol (DON) is one of the most common mycotoxins found in cereal grains and grains contaminated with DON can cause health issues for both humans and animals and result in severe economic losses. Currently there is no feasible method to remediate affected grains. The development of a biological method for detoxification is becoming increasingly more plausible with the discovery of microbes which can transform DON to a relatively non-toxic stereoisomer, 3-epi-DON. Although bacteria capable of detoxifying DON have been known for some time, it is only recently an enzyme responsible was identified. In Devosia mutans 17-2-E-8 (Devosia sp. 17-2-E-8) a two-step DON epimerization pathway, designated as the Dep system, completes this reaction. DepA was recently identified as the enzyme responsible for the conversion of DON to 3-keto-DON, and in this report, DepB, a NADPH dependent dehydrogenase, is identified as the second and final step in the pathway. DepB readily catalyses the reduction of 3-keto-DON to 3-epi-DON. DepB is shown to be moderately thermostable as it did not lose significant activity after a heat treatment at 55 °C and it is amenable to lyophilisation. DepB functions at a range of pH values (5-9) and functions equally well in multiple common buffers. DepB is clearly a NADPH dependent enzyme as it utilizes it much more efficiently than NADH. The discovery of the final step in the DON epimerization pathway may provide a means to finally mitigate the losses from DON contamination in cereal grains through an enzymatic detoxification system. The further development of this system will need to focus on the activity of the Dep enzymes under conditions mimicking industrially relevant conditions to test their functionality for use in areas such as corn milling, fuel ethanol fermentation or directly in animal feed.